2008
DOI: 10.1016/j.juro.2008.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Training on a Virtual Reality Laparoscopic Simulator Improves Performance of an Unfamiliar Live Laparoscopic Procedure

Abstract: Surgical skills acquired as a result of training on a virtual reality laparoscopic simulator are not procedure specific but improve overall surgical skills, thereby translating into superior performance of an unrelated live laparoscopic urological procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Various studies have reported that training using virtual reality simulators has significantly increased skills in laparoscopic urology under real-life conditions. [9,10] Wet laboratory training on live animals The stages in the process of selecting an animal model can be summarised as; 5. Determine the importance of the factors in the application such as procurement, sheltering, caring, and managing animals, equipment, experience, and literature information 6.…”
Section: Dry Laboratory Training With Pelvitrainermentioning
confidence: 99%
“…Various studies have reported that training using virtual reality simulators has significantly increased skills in laparoscopic urology under real-life conditions. [9,10] Wet laboratory training on live animals The stages in the process of selecting an animal model can be summarised as; 5. Determine the importance of the factors in the application such as procurement, sheltering, caring, and managing animals, equipment, experience, and literature information 6.…”
Section: Dry Laboratory Training With Pelvitrainermentioning
confidence: 99%
“…The OSATS tool has demonstrated high reliability and construct validity and is now used as a globally validated rating scale (23 Global assessments are now widely used in the assessment of proficency during training and are used to study the effect that simulated surgical training has on operative skill. Studies by Scott et al, Hamilton et al, Traxer et al and Lucas et al demonstrating the transfer of skill from a simulated environment to the operating room have used a slightly modified version of OSATS with an included parameter of overall performance (24)(25)(26)(27). In the study by Scott et al (26), the modified OSATS showed improvement in four of the eight parameters including the new parameter overall performance.…”
Section: Global Rating Scalesmentioning
confidence: 99%
“…One study (25) provided training for the novice group in laparoscopic cholecystectomy but assessed skill transfer in laparoscopic nephrectomy. The results showed that the group who received time based simulated laparoscopic cholecystectomy training outperformed the control group when a laparoscopic nephrectomy was performed in a porcine model.…”
Section: Vr-to-or Transfermentioning
confidence: 99%
“…68,69 The technical skills acquired during virtual-reality training have been shown to be transferable both to an animal model and to patients in the operating room. [70][71][72][73] In a randomized doubleblinded study, Seymour and colleagues showed that particpants who received low-fidelity virtual-reality training showed improved time to complete laparoscopic cholecystectomy (29% faster than residents not trained using virtual reality), were five times more likely to make progress and six times less likely to make errors compared with residents not trained using virtual reality. 74 These results were replicated in a later randomized blinded controlled trial by Grantcharov and colleagues.…”
Section: Virtual Realitymentioning
confidence: 99%